The academic conceptualisation of ethical clothing: Could it account for the attitude behaviour gap?. Issue 4 (3rd October 2016) - Reimers, Vaughan; Magnuson, Bryce; Chao, Fred
Abstract : Purpose: Despite supposed widespread consumer support for ethical clothing, it still often fails to translate into actual purchase. The purpose of this paper is to determine whether the way in which academics have defined and measured ethical clothing could account for this. Design/methodology/approach: An over reliance on convenience sampling and the use of student samples has also been touted as a possible reason for this attitude-behaviour gap. To address this, this study employed a consumer household sample. It also used a quantitative survey approach to collect its data and structural equation modelling to analyse it. Findings: In contrast to the way in which academics have conceptualised the construct, consumer perceptions of ethical clothing were found to be influenced by four dimensions: environmental responsibility, employee welfare, animal welfare and slow fashion attributes. Originality/value: Ethical clothing has typically been operationalised using just two of these four dimensions. Ironically, one of the two dimensions often overlooked by academics – animal welfare – had the strongest influence on consumer perceptions. Previous academic efforts had never employed more than three dimensions, and yet the results of this study suggest that all four must be present if an item of clothing is to be regarded as "ethical".